Pengaruh Working Capital Management Days Dan Corporate Governance Terhadap Firm Value Pada Perusahaan Pertambangan Yang Terdaftar Di Bei - Gisella Liemanto Lim; Saarce Elsye Hatane (Business Accounting Review, 2020)
This study aimed to examine the direct and significant influence between Working Capital Management and Corporate Governance Disclosure toward Firm Value and also to determine the indirect effect of the influence of Firm Size and Leverage on Firm Value ac Control Variable. The samples used in this research were 30 manufacturing companies listed in Indonesia Stock Exchange starting from 2014-2018. Data processed by using GRETL software version 5.0.       The results of the research found the positive influence between Inventory Days, External Audit and Non-Audit Services and Transparency with Firm Value. There was also a negative influence between Account Receivable days and Structure of the Board and Management on Firm Value. The results also found there is no influence between Account Payable Days and Ownership Structure on Firm Value.